A Study on Security Threats in Manets - Omkar, Vaidya; Amiya, Gautam; Jaisankar, N (International Journal of Computer Sciences and Engineering, 2025)
MANETs have very unique characteristics like dynamic topology, wireless radio medium, limited resources and lack of centralized administration; as a result, they are sensitive to different types of attacks in different layers of protocol stack. Each node in a MANETs is capable of acting as a router. Routing is one of the aspects having various security concerns. MANETs has no rigid line of defense, so, it is accessible to both legitimate network users and malicious attackers. In the presence of mischievous nodes, one of the main challenges in MANETs is to design the robust security solution that can protect MANETs from various routing attacks. This paper present survey of common attacks on network layer namely Black-hole, Wormhole and Gray-hole attack which are serious threats for MANETs. This paper also discusses some proposed solutions which help to detect and prevent these attacks. MANETs can operate in isolation or in coordination with a wired infrastructure, often via a gateway node participating in both networks for traffic relay. This flexibility, along with their self-organizing powers, is one of MANET's biggest strengths, as well as their biggest security weaknesses.